Thermal characteristic reliability of fatty acid binary mixtures as phase change materials (PCMs) for thermal energy storage applications - Fauzi, H.; Metselaar, H.S.C.; Mahlia, T.M.I.; Silakhori, M.; Ong, H.C. (Applied Thermal Engineering, 2015)
The thermal characteristic reliability of two binary mixtures of fatty acid, myristic acid/palmitic acid/ sodium myristate (MA/PA/SM) and myristic acid/palmitic acid/sodium palmitate (MA/PA/SP), were investigated using a thermal cycling test setup for 0, 1000, 2000, 3000, and 3600 heating/cooling cycles. The changes in thermal properties and chemical bonding of both eutectic PCMs were measured using Differential Scanning Calorimetric (DSC) and Fourier Transform Infrared Spectroscopy (FT-IR) analyzer, respectively. MA/PA/SM and MA/PA/SP eutectic mixtures shows only minor changes in phase transition temperature (Tin, Ts) and in latent heat of fusion (ilk). Moreover, the chemical bonding structures of these eutectic PCMs show no degradation and the thermal performance of those PCMs shows a good stability after 3600 thermal cycles. Therefore, it is found that the thermal characteristic stability of prepared MA/PA/SM and MA/PA/SP eutectic mixtures were acceptable for long term performance and economic feasibilities used as a phase change material (PCM) for thermal energy storage (TES) application. (C) 2015 Elsevier Ltd. All rights reserved.